Stochastic Generation of Subsurface Profiles for Realistic Simulation of Through-the-Earth Communication Systems - Josua Daniel Pena Carreno; A. Judson De Barros Braga (International Journal of Antennas and Propagation)
Channel modeling for Through-the-Earth (TTE) communication has mainly been based on deterministic and empirical formulations. Deterministic models are limited to homogeneous rock structures while empirical models are only valid for the same configuration as the measurements that were taken. Given the difficulties in implementing underground measurements taking years to achieve enough database for a variety of mines and depths, we propose, as a more versatile solution, realistic simulations of a variety of underground structures to statistically characterize magnetic field attenuation. An algorithm based on the Monte Carlo method is presented and uses the Finite Element Method (FEM) to compute field propagation through each random structure. An empirical model is produced through simulations, and some metrics are evaluated, such as the median of magnetic field intensity, and the propagation loss, specially at the optimum operation frequency, in which channel variability is less spread when compared to all possible frequencies. This model can be used to estimate link budget for TTE communication in coal mines.